2010
DOI: 10.1007/s12289-010-0867-0
|View full text |Cite
|
Sign up to set email alerts
|

Warpage of Flat Composite Part Induced by Liquid Resin Infusion (LRI) Processes

Abstract: Composite materials manufacturing of high performance part require high cure temperature in a multimaterial environment. It results multi-scale product-process-resources interactions, which are responsible for low dimensional fidelity between the mould and the part shape. Because of the different implementation by LRI processes, warpage cannot be account only for tool-part interaction like by prepreg-autoclave processes. An interaction between the part and the moulding resources are characterized, which is in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This non-uniform stress distribution is locked in as the resin cures and upon removal from the tooling, the resultant bending moment warps the part away from the tooling. When liquid resin infusion processes are used, such as those used in this work where Perrin et al (2010) suggested that the resin distribution media can be another important source of warpage, explaining that the cure shrinkages are too different in the part (high fibre to resin ratio) than in the flow media (high resin to nylon mesh ratio).…”
Section: Visual Observations Of the Manufactured Composite Panelsmentioning
confidence: 89%
“…This non-uniform stress distribution is locked in as the resin cures and upon removal from the tooling, the resultant bending moment warps the part away from the tooling. When liquid resin infusion processes are used, such as those used in this work where Perrin et al (2010) suggested that the resin distribution media can be another important source of warpage, explaining that the cure shrinkages are too different in the part (high fibre to resin ratio) than in the flow media (high resin to nylon mesh ratio).…”
Section: Visual Observations Of the Manufactured Composite Panelsmentioning
confidence: 89%
“…Residual stresses are generally set up during curing and cooling processes of the composites. 13,15,19 These residual stresses could be partially released during de-molding process and lead to unintended deformation of the composite laminates. In this section, the residual strains of the laminates released during post cure process at 120°C were monitored utilizing strain gauges.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 It is clear that residual stresses generated during composite fabrication process are directly related to the processing parameters, such as curing temperature and time, cooling rate, and de-molding temperature. 18 21 Hence, curing and cooling process in rapid hot press process should be designed carefully, and the effects of rapid processing conditions on the properties of composites need to be understood before rapid processing could be practically used in automobile industry. However, less works addressed the residual strains development during rapid curing and cooling process.…”
Section: Introductionmentioning
confidence: 99%